Prognostic significance and therapeutic potential of guanosine triphosphate cyclohydrolase 1 in esophageal squamous cell carcinoma: clinical implications of ferroptosis and lipid peroxidation regulation - Sakano, Masayoshi; Tomita, Yoshinobu; Kanazawa, Takumi; Ishibashi, Sachiko; Ikeda, Masumi; Oshita, Haruna; Hananoi, Yuri; Kato, Yuki; Yamamoto, Kurara; Furukawa, Asuka; Kinoshita, Mayumi; Haruki, Shigeo; et al. (Frontiers in Oncology, 2024)
BackgroundEsophageal cancer, particularly esophageal squamous cell carcinoma (ESCC), is a leading cause of cancer-related death and has a poor prognosis. Despite the advancements in multidisciplinary therapies, resistance to conventional treatments warrants the development of novel therapeutic strategies. Ferroptosis, a form of cell death dependent on intracellular iron, has emerged as a potential mechanism for targeting cancer cells resistant to apoptosis. Guanosine triphosphate cyclohydrolase 1 (GCH1) has been identified as a novel antagonist of ferroptosis; however, its role in ESCC remains unclear. This study aimed to investigate the correlation between the expression and accumulation of the lipid peroxidation markers and regulators, including GCH1, in patients with ESCC and examined their prognostic significance. Furthermore, we investigated the relationship between lipid peroxidation regulators and cell death using an in vitro system to establish the basis for new therapeutic strategies.MethodsWe retrospectively analyzed 312 patients with ESCC who underwent radical esophagectomy at the Tokyo Medical and Dental University. Immunohistochemistry was performed to evaluate the expression of lipid peroxidation markers (4-hydroxy-2-nonenal) and regulators (glutathione peroxidase 4 [GPX4], ferroptosis suppressor protein 1 [FSP1], and GCH1). The correlation between these markers, clinicopathological features, and overall survival was assessed. In vitro experiments were performed using KYSE-150 cells to investigate the effects of GCH1 knockdown and overexpression on cell proliferation, cisplatin-induced cell death, and ferroptosis.ResultsLow GCH1 expression was significantly associated with a poor prognosis in patients with ESCC. GCH1 expression correlated with lymph node metastases, vessel invasion, and the pathological tumor stage. In vitro, GCH1-knockdown cells exhibited increased proliferation and resistance to cisplatin-induced cell death, whereas GCH1 overexpression reduced cell proliferation. Simultaneous inhibition of GPX4 and FSP1 induced mild cell death; however, GCH1 knockdown dramatically enhanced ferroptosis, suggesting a synergistic effect.ConclusionGCH1 is a critical prognostic factor for ESCC and plays a significant role in the regulation of cell proliferation and ferroptosis. Targeting GCH1 in combination with GPX4 and FSP1 inhibitors may offer a novel therapeutic strategy for overcoming resistance in ESCC. Further studies are warranted to elucidate the involved molecular mechanisms and validate these findings in vivo.